Is Islamic Banking Good for Growth? - Imam, Patrick (IMF Working Papers; Working Paper ;, 2015)
The rapid growth of Islamic banking has attracted much attention lately in the economic literature. At the same time, a mature body of the literature has shown that financial development is broadly conducive to economic growth, which raises the question as to whether a similar conclusion holds for Islamic banking. Against this backdrop, this paper investigates the relationship between Islamic banking development and economic growth in a sample of low and middle income countries, using data over the period 1990-2010. The results show that, notwithstanding its relatively small size compared to the economy and the overall size of the financial system, Islamic banking is positively associated with economic growth even after controlling for various determinants, including the level of financial depth. The results are robust across across different specifications, sample composition and time periods.